Hospitalization for COVID-19 in the municipality of Canoas/RS: Delineation of the population profile - Camargo, Miria Elisabete Bairros de; Gasparetto, Carlos Eduardo; Dall’Ago , Lana Caroline Palaver; Coppetti, Liara Eickhoff; Loredo , Paula; Burg, Maria Renita (Seven Editora, 2023)
Introduction: The COVID-19 pandemic started in March 2020 and is marked by a high number of infected. The symptoms of the disease are variable and the most severe cases occurred mainly in elderly patients and those with previous comorbidities. Objectives: To profile infected patients in the city of Canoas/RS, who required hospitalization for COVID-19; whose hospital discharge happened in January 2021. Method: This is a descriptive, exploratory, retrospective and documentary study, with a quantitative approach, where 51 medical records of patients living in Canoas/RS were analyzed, and had the hospital discharge in January 2021 with a positive diagnosis for the COVID-19 virus, at the city´s benchmark hospital. Results: The profile that was found: male, with an average age of 55,6 years old, white and single. The average hospitalization was 6,8 days. About the medications, the most frequently used was dexamethasone and, among other care prescribed after hospital discharge, the most known was the follow-up at the Basic Health Unit. Approximately 34 patients had some comorbidity and, also, more than half had previously used continuous medications. Only three patients in the study responded affirmatively about exposure to COVID-19 and the main symptoms presented by patients in general were dyspnea, cough and fever. Final considerations: The study shows that patients with advanced age and with chronic diseases are at greater risk of developing the severe form of COVID-19. The high rate of transmissibility can be observed by the absence of information regarding the natural history of the disease. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-035